Docker Certified Associate (DCA) certification training course (Packt Publishing, 2022)
Learn to work with Docker and prepare yourself for the Docker Certified Associate Certification exam. About This Video Learn how to install Docker on CentOS using automated scripts Understand the application containerization benefits and drawbacks Explore the various networks on Docker In Detail The Docker Certified Associate (DCA) exam validates your skills as an experienced Docker practitioner, acting as a foundational benchmark for real-world Docker skills across the container industry. Professionals with this Docker certification will set themselves apart as uniquely qualified to run enterprise workloads at scale with Docker Enterprise Edition and can display the certification logo on their resumes and social media profiles. This Docker training is aligned with the Docker Certified Associate (DCA) Certification body and covers the fundamentals of Docker. You will be able to comprehend Docker and its role in the DevOps lifecycle; create images, containers, swarms, volumes, and networks; define Docker security client bundles and client-server authentication; and more. You will learn everything you need to know about Docker Certified Associate (DCA). You will start with the very basics of Docker and understand the difference between Docker and virtualization. You will learn about the advantages of microservices and the components of Docker Engine. Learn and understand the implementation of the Docker engine; understand the installation of Docker on Ubuntu using the Docker repository and using automated scripts. Moving further, you will also learn about Docker client configuration and Docker images. Along the course, you will learn about working with Docker images and how to utilize search in a Registry. You will learn to demonstrate Docker container logs, Docker networks, Docker swarm, and more. By the end of this course, you will be able to comprehend Docker and its role in the DevOps lifecycle and create images, containers, and swarms. Audience Anyone interested in learning Docker will benefit from this Docker certification training. This DCA course is well-suited for freshers, software developers, software engineers, technical leads, and system administrators. Learners need to possess an undergraduate degree or a high school diploma. Knowledge of Linux, including hands-on experience, is required.